تحديد نوع المناخ بإستخدام معامل الجفاف ( ديمارتون ) في محطة نالوت للفترة 1960-2020م (Comprehensive Journal of Science, 2026)
This study aims to determine the climatic type of Nalut station during the period (1960–2020) using the De Martonne Aridity Index, which is based on average temperature and rainfall amounts. The study period was divided into two intervals (1960–1989) and (1990–2020) to examine climatic changes. The results revealed the dominance of a semi-arid climate during most months of the first period, followed by a noticeable shift toward a humid climate in the second period, mainly due to increased rainfall despite rising temperatures. Statistical analysis showed a strong inverse correlation between the aridity index and temperature, and a strong positive correlation between the aridity index and rainfall, confirming that increased precipitation enhances climatic humidity. The findings indicate a clear climatic change in the region, highlighting the need for sustainable environmental planning to address future drought variability.
Keywords: De Martonne Aridity Index, climatic drought, climate change, rainfall, temperature, Nalut station